Intravesical compartments in the bladder can affect microbiological culturing outcome: An experimental study in pigs - Stærk, Kristian; Langhorn, Louise; Nielsen, Lene Feldskov; Andersen, Thomas Emil (Frontiers in Urology, 2023)
Urinary tract infections (UTIs) are one of the most common bacterial infections worldwide. The diagnosis is mainly dependent on the quantitative identification of uropathogens in urine from suspected patients and therefore, it is essential that bacterial titers counts in urine specimens accurately reflects the bacterial population inside the bladder. In this study, we collected the first- and last urine specimens during a single full voiding from pigs with experimentally induced UTI and compared the urine density and bacterial titers counts of the collected specimens. We found that specimens from the same voiding varied in density and in bacterial titers counts by up to several hundreda thousand-fold with significant impact on diagnostic sensitivity, particularly in urines collected by bladder catheter. In conclusion, the porcine bladder can simultaneously contain intravesical compartments of varying density and bacterial titers counts that greatly influences microbiological analysis. The distribution of bacteria in intravesical compartments is critical to consider when using pigs as biomedical models of UTI. Furthermore, the similarities of porcine and human anatomy and physiology, suggest that the results are likely to be translatable to human, in which case potential UTIs could be overlooked by today’s diagnostic procedures.